The case for a job guarantee policy in Germany: A political-economic analysis of the potential benefits and obstacles - Jannik J. Landwehr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
As a bottom-up approach, a Job Guarantee policy can tackle the issue of unemployment on the macroeconomic, socioeconomic, and individual level in a unique way and promote the social inclusion of the unemployed. This paper aims at analysing the potential obstacles - namely inflationary pressure and financing - of a Job Guarantee policy implementation in the case of Germany. A Job Guarantee's impact on inflation depends on excess production capacities of economic sectors as well as collective wage bargaining structures. In this regard, this paper concludes that under a correct policy design inflationary pressure is no major obstacle. Strengthening workers' bargaining power in Germany through a Job Guarantee policy could even contribute to reaching the inflation target and prevent deflation. However, deficiencies of the European institutional setup and the analogous restrictive fiscal mantra at European and national level limit the political scope for financing a Job Guarantee policy. Notwithstanding, a small to medium size Job Guarantee programme - comprising up to all currently unemployed willing to work - is politically and legally feasible.
Keywords: E24; E62; H63; J68; 330; Job Guarantee; Employer-of-Last-Resort; Public Works; Unemployment; Underemployment; Full Employment; Inflation; Fiscal Policy; Debt Brake